Pengembangan Teknologi Tepat Guna Toko Bunga dengan Penerapan Metode CRM Toko Risky Flower Sampit - Seprianson Eliyeser; Dwi Tjahjo Seabtian (STMIK Budi Darma, 2021)
In today's technological era, the development of systems and information technology is very important. What is different from building a system is the function and requirements of the system itself. On the other hand, most people already use computer hardware that already has a system that can access all information quickly and precisely, most of them already have high specifications that can provide information faster when the user needs the information to be used, then the system user it will be easier to do. Risky Flower is a shop that provides several types and sizes of flower boards for parties and events to suit their individual needs. Orders made so far are still not fast because it takes a very long time, where customers must communicate directly to the place of sale of the flower board by choosing the type and size that will be used for the event to be held according to customer needs. With the existence of a system, it is hoped that it can help the process of ordering flower boards and can provide information about what customers will need in making their choices quickly without having to go to the place where the flower board is sold. The proposed system fully uses the web-based Customer Relationship Management (CRM) method.